1999
DOI: 10.1021/la981424y
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Globular Proteins with Surfactants Studied with Fluorescence Probe Methods

Abstract: Steady-state and dynamic fluorescence measurements were used to investigate the interactions and structures of complexes formed between bovine serum albumin (BSA) and anionic, cationic, and nonionic surfactants:  sodium dodecyl sulfate (SDS), N-cetyl-N,N,N-trimethylammonium bromide (CTAB), and octaoxyethylene glycol n-dodecyl ether (C12E8), respectively. The lysozyme (Lys)−SDS complex was also studied. The measurements were carried out at different pH's and ionic strengths. In all systems, micelle-like cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
193
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(210 citation statements)
references
References 60 publications
14
193
1
2
Order By: Relevance
“…DLS studies of CTABGelatin interaction [74,75] showed that beyond critical aggregation concentration gelatin -CTAB complexes were observed to grow significantly and were in equilibrium with CTAB micelles. The micellar shapes were found to be oblate ellipsoidal for CTAB micelles which were explained through the necklace -bead model through co-operative bonding [76]. Hydrophobic interaction may be operating between the hydrophobic part of CTAB and hydrophobic sites on the gelatin chain.…”
Section: Biopolymer Surfactant Interactions 443mentioning
confidence: 93%
See 1 more Smart Citation
“…DLS studies of CTABGelatin interaction [74,75] showed that beyond critical aggregation concentration gelatin -CTAB complexes were observed to grow significantly and were in equilibrium with CTAB micelles. The micellar shapes were found to be oblate ellipsoidal for CTAB micelles which were explained through the necklace -bead model through co-operative bonding [76]. Hydrophobic interaction may be operating between the hydrophobic part of CTAB and hydrophobic sites on the gelatin chain.…”
Section: Biopolymer Surfactant Interactions 443mentioning
confidence: 93%
“…An abrupt increase in, ηr, can be due to the incorporation of halide ion leading to the screening of the electrostatic interaction of surfactant head groups. Decreased head group repulsion favors closer packing of the surfactant monomers and hence induces sphere → rod transition in micelles [76,77]. At higher [CTAB+ NaCl], further increase in size is observed due to formation of polymer -micelle complex.…”
Section: Biopolymer Surfactant Interactions 443mentioning
confidence: 99%
“…Because human serum albumin is physiologically important and easy to isolate and purify, it is often used as a model globulin to study its interaction with surfactants [15][16][17][18]. The thermodynamic properties of the interaction of HSA with two quaternary ammonium gemini surfactants in buffer solution (pH =7.0) were studied by isothermal 030008-2 titration calorimetry at 298.15 K. The results showed that the secondary structure of HSA was changed by the addition of surfactants.…”
Section: Effect Of Surfactant On Humanmentioning
confidence: 99%
“…Surfactants are widely employed in biochemistry and biotechnology for the purpose of protein solubilization, purification, characterization, and protein structure determination (Miksovska, et al, 2006). Surfactant-protein interactions are very common in the fields of medicine, chemistry, biology and so on (Liu et al, 2007;van der Veen et al, 2004;Orioni et al, 2006;Vasilescu et al, 1999;Stenstam et al, 2003). Many approaches have been focused such as the kind of protein-surfactant interaction, the influence of the aggregation state of the surfactant (monomer, pre-micellar aggregate and micelle) on the protein structure, the properties of the surfactant-protein system, the characterization of the interaction sites on the protein surface, the identification of the intermediate protein conformations, etc (Liu et al, 2007;Liu et al, 2005;Ajloo et al, 2002).…”
Section: The Interaction Between Hbgp and Surfactants As Resource Of mentioning
confidence: 99%